Clampless and sutureless laparoscopic partial nephrectomy using monopolar coagulation with or without N-butyl-2-cyanoacrylate - Zhang, Feng (World J Surg Oncol, 2019)
OBJECTIVE: To describe a novel technique for clampless and sutureless laparoscopic partial nephrectomy (LPN) using monopolar coagulation with or without N-butyl-2-cyanoacrylate (NBCA). METHODS: From February 2015 to October 2018, we performed clampless and sutureless LPN using monopolar coagulation with or without NBCA on 142 patients. The tumors were resected with cold scissor. The tumor beds were repeatedly coagulated with a monopolar hook in spray and fulgurate modes. NBCA was sprayed when bleeding was observed after coagulation in 98 patients. We compared outcomes in the NBCA and non-NBCA groups. RESULTS: Mean patient age was 55 years (range 20–86). Mean tumor size was 3.2 cm (range 1.0–10.6). Mean RENAL nephrometry score was 5 (range 4–8). Mean operative time was 120 min (range 40–200). Mean estimated blood loss was 100 ml (range 10–500). Mean eGFR changes were 2.3 ml/min. Two patients had positive surgical margins. Three patients received blood transfusions. No patients had urine leakage. Patients receiving NBCA had larger tumors (3.0 vs 2.0 cm, p < 0.001), higher RENAL nephrometry scores (5.59 vs 4.47, p = 0.004), and higher E item scores (p = 0.009). CONCLUSIONS: Use of monopolar coagulation with NBCA in clampless and sutureless LPN for renal tumors with low RENAL nephrometry scores is safe and effective. For patients with exophytic renal tumors less than 2 cm, NBCA is not necessary.